Applied statistics and probability for engineers - Montgomery, Douglas C; Runger, George C. (Hoboken, NJ : John Wiley and Sons, Inc., 2014)
"This best-selling engineering statistics text provides a practical approach that is more oriented to engineering and the chemical and physical sciences than many similar texts. It is packed with unique problem sets that reflect realistic situations engineers will encounter in their working lives. This text shows how statistics, the science of data is just as important for engineers as the mechanical, electrical, and materials sciences"--
Includes bibliographical references and index.
Keywords: Statistics; Probabilities; TECHNOLOGY & ENGINEERING / Industrial Engineering